2017
DOI: 10.3389/fcimb.2017.00370
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Adenylyl Cyclase Encoded by the Mycobacterium tuberculosis Rv2212 Gene Confers Improved Fitness, Accelerated Recovery from Dormancy and Enhanced Virulence in Mice

Abstract: Earlier we demonstrated that the adenylyl cyclase (AC) encoded by the MSMEG_4279 gene plays a key role in the resuscitation and growth of dormant Mycobacterium smegmatis and that overexpression of this gene leads to an increase in intracellular cAMP concentration and prevents the transition of M. smegmatis from active growth to dormancy in an extended stationary phase accompanied by medium acidification. We surmised that the homologous Rv2212 gene of M. tuberculosis (Mtb), the main cAMP producer, plays similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…We also checked the intracellular concentration of cAMP. Previously we found that the transition of Mtb to the dormant "non-culturable" state correlates with a decrease in the cAMP concentration (Shleeva et al, 2017a). Alternatively, cAMP concentration increases in Msm cells under resuscitation (Shleeva et al, 2013).…”
Section: Resultsmentioning
confidence: 92%
“…We also checked the intracellular concentration of cAMP. Previously we found that the transition of Mtb to the dormant "non-culturable" state correlates with a decrease in the cAMP concentration (Shleeva et al, 2017a). Alternatively, cAMP concentration increases in Msm cells under resuscitation (Shleeva et al, 2013).…”
Section: Resultsmentioning
confidence: 92%
“…. Other adenylate cyclases influencing mycobacterial virulence include Rv2212 (Shleeva et al, 2017) and Rv1675c (Smith et al, 2017). Unlike cAMP, c-di-AMP, and c-di-GMP serve as an alarm signal for the mammalian immune system (Karaolis et al, 2007).…”
Section: The Second Messenger Campmentioning
confidence: 99%
“…Assuming that as longer is the duration of experimental infection, the higher is precision of its dynamic assessment and relevance to the LTBI problem, we began to use M. tuberculosis strains with substantially diminished virulence, which induce very slowly developing disease in mice. Two main approaches of M. tuberculosis H37Rv attenuation were applied: genetic attenuation caused by knocking out genes of the Rpf family involved in regulation of mycobacterial growth [21][22][23], and a prolonged exposure to a gradual acidification in vitro, resulting in a so-called "non-culturable", dormant-like state of mycobacteria [24,25]. Using the first approach, we revealed previously unknown features of early and late lung inflammation that differentiate genetically susceptible and resistant mice.…”
Section: Introductionmentioning
confidence: 99%